Flegmasia cerulea dolens: reporte de un caso y revisión de la literatura - Falcón B., Felipe; Pereda R., M. Lilia; Maripangui D., Maritza; Campos G., Alejandro; Sarmiento G., M. Carolina (Revista Hospital Clínico Universidad de Chile, 2010)
Phlegmasia Caerulea Dolens is a rare complication of deep vein thrombosis. It presents with a sudden onset of pain, swelling, discoloration and arterial compromise of the affected limb. There’s usually history of prothrombotic events such as malignancy, femoral vein catheterism, antiphospholipid syndrome, recent surgery, pregnancy, etc. Left without treatment, it can evolve into gangrene, septic shock and death. Diagnosis usually only requires clinical appreciation. Confirmation can be done with ultrasonographic studies with doppler. Treatment can be both medical and surgically based. Medical therapy can be done with heparin and elevation of the affected limb or the use of thrombolytic, whilst surgical therapy can be either venous thrombectomy or amputation. We present the case of a 57-year old smoker, diabetic, and with systemic lupus erythematosus history female patient, that goes to the emergency room with sudden left leg pain, with cyanosis and absence of distal pulses. Besides she presented with lower respiratory symptoms. Diagnosis was confirmed with ultrasound and CT pulmonary angiography was performed showing pulmonary embolism. Medical treatment was initiated with good response